Adoption Laws and the Rights of Biological Parents: Ethical and Legal Considerations - Ahmad Yusof; Budi Santoso (International Journal of Social Welfare and Family Law, 2024)
This article analyzes the ethical and legal complexities surrounding adoption laws, focusing on the rights of biological parents in the adoption process. Through a review of adoption policies from various countries, the study explores issues such as consent, open vs. closed adoption, and post-adoption contact. Findings suggest that balancing the rights of biological parents with the best interests of the child requires nuanced legal frameworks.